2021
DOI: 10.1111/ijd.15770
|View full text |Cite
|
Sign up to set email alerts
|

Mucha‐Habermann disease: a pediatric case report and proposal of a risk score

Abstract: Febrile ulceronecrotic Mucha-Habermann disease (FUMHD) is a rare inflammatory dermatological disease. A case of a 13-year-old boy with FUMHD possibly triggered by mycoplasma infection is presented. Based on FUMHD cases identified in a MEDLINE literature search, demographic, treatment, and outcome data were analyzed. An FUMHD mortality risk score is proposed based on the likelihood ratios of risk factors for a fatal outcome. Our FUMHD case had marked leukopenia and thrombocytopenia at admission. He recovered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
(39 reference statements)
0
11
1
Order By: Relevance
“…Blohm et al suggested a mortality risk score based on increased age, systemic involvement, and mucosal involvement increasing the mortality risk. 11 Although increased age and systemic involvement is related to increased risk of mortality in this systematic review, mucosal involvement did not appear to be associated with mortality risk and was proportionally reported in the resolved and fatal group.…”
Section: Risk Factors For Poor Prognosiscontrasting
confidence: 50%
See 3 more Smart Citations
“…Blohm et al suggested a mortality risk score based on increased age, systemic involvement, and mucosal involvement increasing the mortality risk. 11 Although increased age and systemic involvement is related to increased risk of mortality in this systematic review, mucosal involvement did not appear to be associated with mortality risk and was proportionally reported in the resolved and fatal group.…”
Section: Risk Factors For Poor Prognosiscontrasting
confidence: 50%
“…A potential trigger was identified in 17.6% (12/68) of FUMHD cases and were most commonly infectious in etiology including mycoplasma, 11 Varicella Zoster Virus (VZV), 33 parvovirus B19, 45 Epstein- Barr Virus (EBV), 30 , 51 , 66 Herpes Simplex Virus 2 (HSV-2), 56 Cytomegalovirus (CMV), 57 and adenovirus type II. 24 Other potential triggers reported include a spider bite, 38 measles vaccine, 67 and nonfebrile enteritis.…”
Section: Summary Of Disease Coursementioning
confidence: 99%
See 2 more Smart Citations
“…Since the disease discovery by Degos et al in 1966, there have been approximately 121 reported cases in the literature, including this case. The overall mortality rate is 12.4%; most deaths occurred in adults [2, 3] . Fever and acute progressive generalized eruption of necrotic papules that rapidly evolve to form necrotic plaques and ulcers that may reach up to a few centimeters in diameter are classic for this disease.…”
Section: Introductionmentioning
confidence: 99%